Indigenous Experiences of the Mining Resource Cycle in Australia’s Northern Territory: Benefits, Burdens and Bridges? - Carson, Dean; Govan, Jeanie; Carson, Doris (Journal of Northern Studies, 2019)
This paper proposes a model of how Indigenous communities may engage with the mining sector to better manage local development impacts and influence governance processes. The model uses a resource lifecycle perspective to identify the various development opportunities and challenges that remote Indigenous communities and stakeholders may face at different stages of the mining project. The model is applied to two case studies located in the Northern Territory of Australia (Gove Peninsula and Ngukurr) which involved different types and scales of mining and provided different opportunities for development and governance engagement for surrounding Indigenous communities. Both cases emphasise how the benefits and burdens associated with mining, as well as the bridges between Indigenous and outsider approaches to development and governance, can change very quickly due to the volatile nature of remote mining operations. There is thus a need for more flexible agreements and more dynamic relationships between Indigenous, mining and other governance stakeholders that can be adjusted and renegotiated as the conditions for mining change. The final discussion reflects on how the model may be applied in the context mining governance and Indigenous stakeholder engagement in the Fennoscandian north.